2009
DOI: 10.1016/j.ultrasmedbio.2009.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Focused Ultrasound Effects on Nerve Action Potential in vitro

Abstract: Minimally invasive applications of thermal and mechanical energy to selective areas of the human anatomy have led to significant advances in treatment of and recovery from typical surgical interventions. Image-guided focused ultrasound allows energy to be deposited deep into the tissue, completely noninvasively. There has long been interest in using this focal energy delivery to block nerve conduction for pain control and local anesthesia. In this study, we have performed an in vitro study to further extend ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
126
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(137 citation statements)
references
References 30 publications
9
126
2
Order By: Relevance
“…15,25,26,70,86 Other studies have demonstrated activation of neural tissue, both peripherally and in the CNS. 32,50,81 These effects have been postulated to occur as a result of mechanical stimuli (reversible) and thermal ablation (potentially irreversible).…”
Section: Neuromodulation and Epilepsymentioning
confidence: 99%
“…15,25,26,70,86 Other studies have demonstrated activation of neural tissue, both peripherally and in the CNS. 32,50,81 These effects have been postulated to occur as a result of mechanical stimuli (reversible) and thermal ablation (potentially irreversible).…”
Section: Neuromodulation and Epilepsymentioning
confidence: 99%
“…In conventional FUS stimulation systems, a single FUS transducer with a fixed focus is used. (15)(16)(17)(18)(19) In this configuration, the transducer must be geometrically shifted for the planar control of the focal point. In addition, it is difficult to finely adjust a depth of focus (DOF) because it is only discretely controllable by replacing the transducer.…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed FUS can stimulate the receptor and conductive nerve structures of humans and animals as well as the neurons of the central nervous system of invertebrates. 135 Colucci et al 136 more recently studied the application of FUS on sciatic nerves in bullfrogs. The nerve action potential was shown to decrease in the experiments and correlated with temperature elevation measured in the nerve.…”
mentioning
confidence: 99%
“…These results indicate that a thermal mechanism of FUS can be used to block nerve conduction, either temporarily or permanently. 136 Foley et al 137 investigated the effects of various exposures (intensity, duration) of HIFU on sciatic nerve conduction in rats, with the aim to identify HIFU exposures that produce biological effects ranging from partial to complete conduction block, indicating potential use of HIFU as an alternative to current clinical methods of inducing nerve conduction block. 137 HIFU was demonstrated to attenuate neural responses of sciatic nerves isolated from normal or neuropathic rats, with diabetic nerves being less suppressed by HIFU and more vulnerable to permanent damage.…”
mentioning
confidence: 99%